Dynamic Risk Stratification of Patient Long-Term Outcome After Pulmonary Endarterectomy: Results From the United Kingdom National Cohort. Issue 18 (3rd May 2016) - Cannon, John E.; Su, Li; Kiely, David G.; Page, Kathleen; Toshner, Mark; Swietlik, Emilia; Treacy, Carmen; Ponnaberanam, Anie; Condliffe, Robin; Sheares, Karen; Taboada, Dolores; Dunning, John; et al.
Abstract : Background—: Chronic thromboembolic pulmonary hypertension results from incomplete resolution of pulmonary emboli. Pulmonary endarterectomy (PEA) is potentially curative, but residual pulmonary hypertension following surgery is common and its impact on long-term outcome is poorly understood. We wanted to identify factors correlated with poor long-term outcome after surgery and specifically define clinically relevant residual pulmonary hypertension post-PEA. Methods and Results—: Eight hundred eighty consecutive patients (mean age, 57 years) underwent PEA for chronic thromboembolic pulmonary hypertension. Patients routinely underwent detailed reassessment with right heart catheterization and noninvasive testing at 3 to 6 months and annually thereafter with discharge if they were clinically stable at 3 to 5 years and did not require pulmonary vasodilator therapy. Cox regressions were used for survival (time-to-event) analyses. Overall survival was 86%, 84%, 79%, and 72% at 1, 3, 5, and 10 years for the whole cohort and 91% and 90% at 1 and 3 years for the recent half of the cohort. The majority of patient deaths after the perioperative period were not attributable to right ventricular failure (chronic thromboembolic pulmonary hypertension). At reassessment, a mean pulmonary artery pressure of ≥30 mm Hg correlated with the initiation of pulmonary vasodilator therapy post-PEA. A mean pulmonary artery pressure of ≥38 mm Hg and pulmonary vascular resistance ≥425 dynes·s −1 ·cm −5 at reassessment correlated with worse long-term survival. Conclusions—: Our data confirm excellent long-term survival and maintenance of good functional status post-PEA. Hemodynamic assessment 3 to 6 months and 12 months post-PEA allows stratification of patients at higher risk of dying of chronic thromboembolic pulmonary hypertension and identifies a level of residual pulmonary hypertension that may guide the long-term management of patients postsurgery. Abstract : Supplemental Digital Content is available in the text.